2015
DOI: 10.1002/hbm.23053
|View full text |Cite
|
Sign up to set email alerts
|

Neural representation of emotion regulation goals

Abstract: The use of top-down cognitive control mechanisms to regulate emotional responses as circumstances change is critical for mental and physical health. Several theoretical models of emotion regulation have been postulated; it remains unclear, however, in which brain regions emotion regulation goals (e.g., the downregulation of fear) are represented. Here, we examined the neural mechanisms of regulating emotion using fMRI and identified brain regions representing reappraisal goals. Using a multimethodological anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 87 publications
(186 reference statements)
7
52
0
1
Order By: Relevance
“…As such, the middle temporal gyrus, with projects to the hippocampus and amygdala, is also of interest in that it is implicated in auditory expectation [39], which in individuals with PTSD, might be hyperactive in response to an aversive auditory stimulus. In addition, recent evidence suggests the inferior parietal lobe is associated with successful emotion regulation [40], and is activated in response to an aversive stimulus (shock) [41]. Based on this evidence, these regions are of particular interest to the current study.…”
Section: Introductionmentioning
confidence: 93%
“…As such, the middle temporal gyrus, with projects to the hippocampus and amygdala, is also of interest in that it is implicated in auditory expectation [39], which in individuals with PTSD, might be hyperactive in response to an aversive auditory stimulus. In addition, recent evidence suggests the inferior parietal lobe is associated with successful emotion regulation [40], and is activated in response to an aversive stimulus (shock) [41]. Based on this evidence, these regions are of particular interest to the current study.…”
Section: Introductionmentioning
confidence: 93%
“…(2012) study on metaphorical and literal NNCs which also observed enhanced left amygdala activation for the former, and the meta-analysis of 23 neuroimaging studies on the comprehension of figurative statements (i.e., metaphors, idioms, proverbs, sarcastic, and ironic statements), in which activation of the left amygdala was reported for the contrast between figurative and literal statements (Bohrn et al, 2012a). Perhaps, given that amygdala activation is also associated with reward, if the amygdala is active in figurative language processing, it is being allowed to be so because the control regions of the prefrontal cortex-amygdala network linked to emotion regulation (e.g., Morawetz et al, 2016) detected positive affect. This might imply that metaphors and figurative language in general are, at least on an implicit neuronal level, more pleasant 5 .…”
Section: Multiword Expressionsmentioning
confidence: 99%
“…This is in line with this notion that reduced precision in prior expectations is a result of attenuation in higher hierarchical brain regions (Adams et al, 2016), such as inferior frontal regions (Barbalat et al, 2013;Dzafic et al, 2016;Summerfield and Koechlin, 2008). The right inferior frontal gyrus (IFG) and the insula are neighbouring regions, with roles in higher cognitive processing, such as inhibitory control (Aron et al, 2004;Forstmann et al, 2008), emotion regulation (Morawetz et al, 2016), and emotional awareness (Gu et al, 2013). Activity in the inferior parietal lobule has been associated with the evaluation of prior expectations (Corbetta et al, 2008;O'Connor et al, 2010).…”
Section: Discussionsupporting
confidence: 76%